2018
DOI: 10.1007/s00401-018-1821-3
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxymethylcytosine preferentially targets genes upregulated in isocitrate dehydrogenase 1 mutant high-grade glioma

Abstract: Gliomas demonstrate epigenetic dysregulation exemplified by the Glioma CpG Island Methylator Phenotype (G-CIMP) seen in IDH1 mutant tumors. 5-Hydroxymethylcytosine (5hmC) is implicated in glioma pathogenesis; however, its role in IDH1 mutant gliomas is incompletely understood. To characterize 5hmC in IDH1 mutant gliomas further, we examine 5hmC in a cohort of IDH1 mutant and wild-type high-grade gliomas (HGG) using a quantitative locus-specific approach. Regions demonstrating high 5hmC abundance and differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 80 publications
5
24
0
Order By: Relevance
“…A modest increase of PDGFRA transcripts was also observed in IDH-mutant glioma when compared with IDH-wild-type glioma (80). Furthermore, 5hmC enrichment in gene body regions correlated significantly with the upregulation of genes, such as LGR5 (leucine-rich repeat-containing G-protein-coupled receptor 5), in IDH-mutant glioma (81). It remains unclear, however, whether these epigenetic targets are essential to IDH-mutant gliomagenesis.…”
Section: Does Idh1 Mutation-induced Epigenetic Reprogramming Drive Glmentioning
confidence: 99%
“…A modest increase of PDGFRA transcripts was also observed in IDH-mutant glioma when compared with IDH-wild-type glioma (80). Furthermore, 5hmC enrichment in gene body regions correlated significantly with the upregulation of genes, such as LGR5 (leucine-rich repeat-containing G-protein-coupled receptor 5), in IDH-mutant glioma (81). It remains unclear, however, whether these epigenetic targets are essential to IDH-mutant gliomagenesis.…”
Section: Does Idh1 Mutation-induced Epigenetic Reprogramming Drive Glmentioning
confidence: 99%
“…Many tumors, and especially gliomas, have been characterized by extensive global DNA hypomethylation, associated with aberrant activation of genes and noncoding regions (Chou et al, ; Chu et al, ; Felsberg et al, ; Jia et al, ; Sharma, Kelly, & Jones, ; Uhlmann et al, ; Watanabe & Maekawa, ; Zhang et al, ). Inversely, 5hmC enrichment, potentially allowing gene expression activation, has also been detected in enhancers implicated in glioma pathogenesis (Glowacka et al, ; Johnson et al, ). A number of studies have also shown that the significant DNA methylation changes observed in Schwann cell tumors are likely to contribute to their pathogenesis, as well as aid in their classification.…”
Section: The Role Of Dna Methylation In Schwann Cell and Oligodendrogmentioning
confidence: 99%
“…At an individual CpG site, both 5-mC and 5-hmC can contribute to gene regulation, but none of the available bioinformatics tools provide a function for co-analyzing 5-mC and 5-hmC β values. As a result, existing studies have focused on either examining the distribution of 5-hmC across the genome in isolation (Green et al, 2016; Johnson et al, 2016; Hernandez Mora et al, 2018) or treating 5-mC and 5-hmC β values as independent variables, analyzing each epigenetic mark as a separate dataset to identify differentially methylated and hydroxymethylated regions (Glowacka et al, 2018; Zhang et al, 2018). While there is utility to both of these approaches, the results are difficult to reconcile into a clear picture of the underlying biology for two main reasons: 1) the methodological and biological interdependence of 5-mC and 5-hmC and 2) the different distributions of β mC and β hmC .…”
Section: Problems In 5-methylcytosine and 5-hydroxymethylcytosine Datmentioning
confidence: 99%